Development of Maintenance Scheduling Model for the Safety Operational of Ship Machinery - Handani, Dhimas Widhi; Uchida, Makoto (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2024)
Risk management of ship machinery is an important issue since machinery out of order can run into danger, especially for ships at sea. This paper implements risk based maintenance (RBM) to minimize the frequency and consequences of ship machinery failure. Not only the common steps of RBM, such as identification of problem, risk assessment, risk evaluation, and maintenance planning are conducted, but this paper also proposes a new model called ship position estimation. The preliminary identification i.e. identification of failure causes and symptoms as well as the history of failure time will be looked at first. In the risk assessment, quantification of the consequences of failure (Cof) considers system performance loss, while the probability of failure (Pof) is obtained from the reliability analysis of the failure time history. Risk evaluation compares the result of the risk assessment with the risk acceptance criteria in order to determine the level of risk. The proposed model of ship position estimation recognizes the ship position on the voyage when the analyzed machinery is in a high level of risk. Maintenance planning is further carried out to keep the machinery under the risk acceptance level. This paper utilizes a method called system dynamics to create simulation for each step of the RBM. As a case study, the parts of the pumps in the main engine cooling system are analyzed. The result of this paper is a proposed maintenance interval which is reasonable enough compared with the standard for pump maintenance. Additionally, the ship position is included when the pump reaches a high level of risk.